MYOCARDIAL DYSTROPHY IN CAMEL CALVES IN THE UNITED ARAB EMIRATES (FIELD CASES) - Khouly, A. A. El; Abbas, T. A.; Moustafa, T. (Emirates Journal of Food and Agriculture, 2017)
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